2021
DOI: 10.1039/d1nr03855a
|View full text |Cite
|
Sign up to set email alerts
|

Exposing the trion's fine structure by controlling the carrier concentration in hBN-encapsulated MoS2

Abstract: Atomically thin materials, like semiconducting transition metal dichalcogenides, are highly sensitive to the environment.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 59 publications
0
13
0
Order By: Relevance
“…For instance, recent experiments in ML MoS 2 revealed that doping effects drastically modify the exciton and trion g-factors 84 and that the fine structure of trions is indeed relevant, with different g-factors associated to different trion states. 85 Furthermore, recent calculations have shown that the interplay of doping and dielectric confinement can significantly alter the fine structure of excitons and trions. 86 Although there has been some recent developments on the theory of magneto-excitons [87][88][89] and doping effects on trions, 77,86,90 a more complete picture that incorporates magnetic field, strain effects, doping, and dielectric confinement on an equal footing is still missing.…”
Section: Magneto-opticsmentioning
confidence: 99%
“…For instance, recent experiments in ML MoS 2 revealed that doping effects drastically modify the exciton and trion g-factors 84 and that the fine structure of trions is indeed relevant, with different g-factors associated to different trion states. 85 Furthermore, recent calculations have shown that the interplay of doping and dielectric confinement can significantly alter the fine structure of excitons and trions. 86 Although there has been some recent developments on the theory of magneto-excitons [87][88][89] and doping effects on trions, 77,86,90 a more complete picture that incorporates magnetic field, strain effects, doping, and dielectric confinement on an equal footing is still missing.…”
Section: Magneto-opticsmentioning
confidence: 99%
“…Within this still debated picture, the role played by intrinsic doping in the metallization process has never been adequately considered, although experimental evidence indicates that defect-related intra-gap levels strongly contribute to the optical and electronic response of semiconducting TMDs 16 , 17 . Photoluminescence (PL) spectra of few-layers compounds exhibit excitonic bands ascribable to radiative recombination processes involving doping states 18 20 , and resistivity measurements show that these extra levels significantly modify the transport properties of the samples, even when the doping is unintentional and, thus, the correspondent carrier density very low 17 .…”
Section: Introductionmentioning
confidence: 99%
“…In addition to neutral excitons, a manifold of exciton complexes may be formed with binding energies of tens of meV [6][7][8] ; however, their identification in optical spectra was beyond the reach of simple structures exfoliated directly on standard SiO 2 /Si substrates 9 . Recent progress in elaborating high-quality van der Waals (vdW) heterostructures based on hBN-encapsulated TMDC monolayers allows for observing the subtle optical properties of the exciton complexes thus offering the exploration of many-body effects including electron-electron and electron-phonon interactions [10][11][12][13][14][15][16][17] .…”
Section: Upconversion Photoluminescence Excitation Reveals Exciton-tr...mentioning
confidence: 99%
“…Recent progress in elaborating high-quality van der Waals (vdW) heterostructures based on hBN-encapsulated TMDC monolayers allows for observing the subtle optical properties of the exciton complexes thus offering the exploration of many-body effects including electron-electron and electron-phonon interactions [10][11][12][13][14][15][16][17] . For W-based vdW structures, electron-electron interactions manifest themselves in a trion photoluminescence (PL) line splitting into an inter-valley triplet and intra-valley singlet whose energies are separated by about 6 meV 6,7,18 . Alternatively, the electron-electron coupling may yield the observation of the biexciton fine structure 19 .…”
Section: Upconversion Photoluminescence Excitation Reveals Exciton-tr...mentioning
confidence: 99%